Tradición y novedad en las leyes contra la magia y los paganos de los emperadores cristianos - Salinas de Frías, Manuel (Antigüedad y Cristianismo, 1990)
The legislation against magic practices and paganism of the Christian emperors presents certain aspects of continuity and at the same time a rupture respecting what was the usual practice of the magistrates and Roman emperors in regard to the religio and perstitio. Although, from the political point of view, there exists a certain degree of continuity with the preceeding period which should be evaluated in order to understand the legislation of the Christian emperors, the adoption of Christianism interupts this alterating the image of the historical period and the tradional respect towards the mores which also implicated the religion.